Understanding farmers' intentions to follow a nutrient management plan using the theory of planned behaviour. (June 2019) - Daxini, Amar; Ryan, Mary; O'Donoghue, Cathal; Barnes, Andrew P.
Highlights: TPB used to identify variables influencing farmers' intentions to follow a NMP. Attitude, perceived control and subjective norm positively influence intentions. Subjective norm has a positive effect on attitude and perceived control. Policy and trusted information sources play a role in determining perceptions. Abstract: Farmer decision making in relation to chemical fertiliser and manure use is of great concern to policy makers. Inefficient use can lead to both environmental pollution and financial losses to farmers. Following a nutrient management plan (NMP) can help to mitigate these impacts and improve farm incomes. As the use of NMPs remains below expectation globally, this study aims to provide insights into the drivers of farmers' intentions to follow a NMP and to understand how behavioural change can be encouraged. An extended version of the theory of planned behaviour is adopted and structural equation modelling is used to analyse survey data collected from a sample of Irish farmers. Results show that intention to follow a NMP is primarily driven by perceived behavioural control (ease/difficulty) over following a NMP, followed by subjective norm (social pressure) and finally attitude (negative/positive evaluation) towards following a NMP. We also find that subjective norm is an important predictor of both attitude and perceived behavioural control. Furthermore, policies that require certain farmers to develop a NMP on a mandatory basis, plays a significant role in influencing famers' attitude, subjective norm and perceived behavioural control. Finally, trust in technical sources of information (e.g. advisor and discussion group) is found to be a more influential determinant of farmers' attitude, subjective norm and perceived behavioural control than trust in social information sources (e.g. family and the media). These results provide a comprehensive understanding of the variables driving farmers' intentions to follow a NMP and highlight the importance of both socio-psychological and institutional variables in the analysis of farmer decision making.